2021
DOI: 10.1093/jxb/erab407
|View full text |Cite
|
Sign up to set email alerts
|

BnaC7.ROT3, the causal gene of cqSL-C7, mediates silique length by affecting cell elongation in Brassica napus

Abstract: Siliques are a major carbohydrate source of energy for later seed development in rapeseed (Brassica napus). Thus, silique length (SL) has received great attention from breeders. We previously detected a novel quantitative trait locus cqSL-C7 that controls SL in B. napus. Here, we further validated the cqSL-C7 locus and isolated its causal gene (BnaC7.ROT3) by map-based cloning. In Zhongshuang11 (parent line with long siliques), BnaC7.ROT3 encodes the potential cytochrome P450 monooxygenase CYP90C1, whereas in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…However, overexpressing the gene in the short silique parental line G120 did not have any impact on the phenotype. Further studies revealed that this was due to a single nucleotide deletion in the fifth exon caused a functional alteration in BnC7.ROT3 (Zhou et al, 2022). The number of seeds per silique (NSS) is also a key factor determining overall yield.…”
Section: Silique Developmentmentioning
confidence: 99%
“…However, overexpressing the gene in the short silique parental line G120 did not have any impact on the phenotype. Further studies revealed that this was due to a single nucleotide deletion in the fifth exon caused a functional alteration in BnC7.ROT3 (Zhou et al, 2022). The number of seeds per silique (NSS) is also a key factor determining overall yield.…”
Section: Silique Developmentmentioning
confidence: 99%
“…Rapeseed ( Brassica napus L.) is a major oilseed crop and is also used as animal feed and in biodiesel production globally. Developing a high-yielding rapeseed variety has been an important goal to meet the increasing vegetable oil demand 1 , 2 . Rapeseed yield should be improved by increasing the seed number per silique (SPS), which is one of the three direct yield-related components, with the other being silique number and seed weight 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, BnaC9.SMG7b associated with SPS was identified on chromosome C9 of rapeseed using a map-based cloning strategy 10 . Furthermore, two other major QTL associated with VSL were identified on chromosome C7 ( BnaC7.ROT3 ) and A9 ( BnaA9.CYP78A9 ) of rapeseed and were cloned and characterized using map-based cloning 2 , 9 . Although a few candidate genes for silique traits have been cloned and functionally characterized, key candidate genes for silique traits, especially for SDPS, remain undiscovered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peanut shell is developed from the ovary wall, which protects peanut seeds from biotic and abiotic stresses and continuously provides nutrients for seed development ( Bruce et al, 1975 ). Large shells also provide more environmental space and nutrients for seeds, which are considered a favorable trait for yield improvement ( Zhou et al, 2022 ). The seed develops from double fertilization and seed size is determined when the endosperm cellularization is completed ( Garcia et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%